Synergistically modulating the electronic structure of Cr-doped FeNi LDH nanoarrays by O-vacancy and coupling of MXene for enhanced oxygen evolution reaction. (15th January 2023) - Yan, Liang; Du, Ziping; Lai, Xinyue; Lan, Jieyi; Liu, Xijun; Liao, Jinyun; Feng, Yufa; Li, Hao
Abstract: Water splitting is an environmentally friendly method of hydrogen generation. However, it is severely limited by the slow anodic oxygen evolution reaction (OER). Iron-nickel layered double hydroxides (FeNi LDH) are promising electrocatalysts for OER, but their intrinsically low electrical conductivity and activity limit the practical applications. Herein, chromium-doped FeNi LDH nanoarrays in situ vertically grown on the surface of the Ti3 C2 Tx MXene (Cr-FeNi LDH/MXene) are successfully synthesized. Remarkably, the robust interaction and electrical coupling between Cr–FeNi LDH and MXene, as well as conspicuous charge transfer and the oxygen vacancies optimizing the adsorption free energy of intermediates, equip the nanocomposites with brilliant catalytic activity and stability toward OER. Thus, the optimized Cr–FeNi LDH/MXene shows a considerable boost in the OER, which affords low overpotential (232 mV at 10 mA cm −2 ) and excellent durability. This work offers a new path to designing highly efficient and earth-abundant catalysts for water splitting and beyond. Graphical abstract: Image 1 Highlights: In situ grown Cr doping FeNi LDH on MXene was facilely synthesized. There are abundant oxygen vacancies in Cr–FeNi LDH/MXene. Synergy between oxygen vacancies and MXene improves the OER kinetics and activities. Cr-FeNi LDH/MXene exhibited excellent OER activity and stability.